Experimental Investigation of the Fatigue Behavior of Basalt Fiber Reinforced Polymer Grid-Concrete Interface. (23rd April 2020) - Wen, Bo; Wan, Chunfeng; Liu, Lin; Fang, Da; Yang, Caiqian
Abstract : Fatigue behavior is an important factor for mechanical analysis of concrete members reinforced by basalt fiber reinforced polymer (BFRP) grid and polymer cement mortar (PCM) and plays a critical role in ensuring the safety of reinforced concrete bridges and other structures. In this study, on the basis of the static loading test results of concrete specimens reinforced by BFRP grid and PCM, a series of fatigue tests with different loading levels were conducted on interfaces between BFRP grid and concrete to investigate the fatigue behavior of BFRP grid-concrete interfaces. The test results indicate that with high loading level, the fatigue failure mode of interface is interfacial peeling failure while it transforms to the fatigue fracture of the BFRP grid under low loading level. The fatigue life ( S-N ) curves of BFRP grid-concrete interface are obtained and fitted in stages according to different failure modes, and the critical point of the two failure modes is pointed out. The relative slip evolution of interface during fatigue is further revealed in different stages with two failure modes, and the law of interface strain is studied with the increase of fatigue times. The relation of effective bonding length of interface and fatigue times is also described.